Development of Two-Stage Transportation Problem Model with Fixed Cost for Opening the Distribution Centers - S. Santoso; Rainisa Maini Heryanto (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2022)
The Two-Stage Transportation Problem (TSTP) is a model of product transportation in the supply chain. The transportation starts from the factory to customers through a distribution center (DC), which considers the fixed cost of opening a DC, the transportation cost per unit from a certain factory to a certain DC, and the transportation cost per unit from a certain DC to certain customers. This study develops a model by allowing direct delivery from the factory to the customer. From the numerical example given, the proposed model that allows direct delivery from the factory to a customer could result in a total distribution cost that is minimized to the initial model. Both models were compared with calculation using Lingo 19.0. The model developed is expected to provide options and consideration for the management to determine the right distribution and logistics strategy for their products.